2018
DOI: 10.1021/acs.jpcb.8b01179
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Metabolism of Omeprazole by Cytochrome P450 2C19 and 3A4: Mechanistic Insights from DFT Study

Abstract: The efficacy of S-omeprazole as a proton pump inhibitor compared with that of its enantiomer R-omeprazole is studied using density functional theoretical calculations. The pharmacokinetic studies suggest that the efficacy of S-omeprazole presumably depends on metabolic pathway and excretion from the human body. The density functional theory calculations at SMD-B3LYP-D3/6-311+G(d,p)/LANL2DZ//B3LYP/6-31G(d)/LANL2DZ with triradicaloid model active species, [PorFe(SH)O], of CYP2C19 enzyme with high-spin quartet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Since iloperidone is both a substrate and an inhibitor of CYP3A4 and CYP2D6, it seems possible that the neuroleptic can also inhibit its own metabolism. Iloperidone is also expected to moderately alter the exposure to drugs primarily cleared by CYP2C19 such as diazepam, omeprazole, mephenytoin or tricyclic antidepressants [29][30][31][32]. The magnitude of interaction may be more pronounced if alternative metabolic pathways are inhibited simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Since iloperidone is both a substrate and an inhibitor of CYP3A4 and CYP2D6, it seems possible that the neuroleptic can also inhibit its own metabolism. Iloperidone is also expected to moderately alter the exposure to drugs primarily cleared by CYP2C19 such as diazepam, omeprazole, mephenytoin or tricyclic antidepressants [29][30][31][32]. The magnitude of interaction may be more pronounced if alternative metabolic pathways are inhibited simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the enantioselective interaction of verapamil and amlodipine with HSA showed that ( R )-(+)-verapamil has stronger bind to HSA compared to ( S )-(-)-verapamil, while ( S )-(-)-amlodipine has a stronger bind than the ( R) -enantiomer [ 26 ]. In another study, the binding of ( S )-omeprazole (esomeprazole) and ( R )-enantiomer to HSA, under simulated physiological conditions, demonstrated that ( R )-omeprazole had higher binding constants than ( S )-omeprazole [ 27 ]. Enantioselectivity binding to HSA was also observed for xanthone derivatives [ 28 ], a promising class of compounds in medicinal chemistry [ 29 , 30 ].…”
Section: Enantioselectivity In Drug Pharmacokineticsmentioning
confidence: 99%
“…Omeprazole is administrated as racemate or enantiomerically pure. However, pharmacokinetic studies suggested that the efficacy of the ( S )-omeprazole (esomeprazole) as a proton pump inhibitor compared to the ( R )-omeprazole may be dependent on the metabolic pathway [ 27 ]. Metabolism studies have demonstrated enantioselective biotransformation of ( R )-omeprazole and ( S )-omeprazole by several known enzymes belonging to the cytochrome P450 (CYP) family, such as CYP2C19, CYP2C9, CYP3A4 and CYP2D6.…”
Section: Enantioselectivity In Drug Pharmacokineticsmentioning
confidence: 99%
See 2 more Smart Citations